(2,4-3 1/2):(-1 13/20)+5 2/6 * (- 5/32) = (-1 1/10) : (-1 13/20) + (-5/6) = 2/3 + (-5/6) = -1/6
ответ: -1/6
(2,4 - 3 1/2) : (-1 13/20) + 5 2/6 · (-5/32) = -1/6
1) 2,4 - 3 1/2 = 2 4/10 - 3 1/2 = 2 4/10 - 3 5/10 = -1 1/10
2) -1 1/10 : (-1 13/20) = -11/10 : (-33/20) = 11/10 · 20/33 = (1·2)/(1·3) = 2/3
3) 5 2/6 · (-5/32) = 32/6 · (-5/32) = -5/6
4) 2/3 + (-5/6) = 4/6 - 5/6 = -1/6
ответ: -1/6.
(2,4-3 1/2):(-1 13/20)+5 2/6 * (- 5/32) = (-1 1/10) : (-1 13/20) + (-5/6) = 2/3 + (-5/6) = -1/6
ответ: -1/6
(2,4 - 3 1/2) : (-1 13/20) + 5 2/6 · (-5/32) = -1/6
1) 2,4 - 3 1/2 = 2 4/10 - 3 1/2 = 2 4/10 - 3 5/10 = -1 1/10
2) -1 1/10 : (-1 13/20) = -11/10 : (-33/20) = 11/10 · 20/33 = (1·2)/(1·3) = 2/3
3) 5 2/6 · (-5/32) = 32/6 · (-5/32) = -5/6
4) 2/3 + (-5/6) = 4/6 - 5/6 = -1/6
ответ: -1/6.